Answer:
y = -1, x = -2
Step-by-step explanation:
First, multiply the top equation by 2 to make 3x become 6x:
6x - 8y = -4
Second, multiply the bottom equation by 3 to make -2x become -6x:
9y - 6x = 3
Add the two equations together, and you get:
y = -1
Plug in y as -1 into the first or second equation:
3x - 4(-1) = -2
OR
3(-1) - 2x = 1
x = -2
We set up a proportion: 80/?= 32/100
Cross multiply: 32*?= 80*100
⇒ ?= 80*100/32= 250
80 is 32% of 250.
Answer:
simply multiply each number by -2
Step-by-step explanation:
7 * -2 = -14 -14 * -2
brainliest answer plz!
The answer to the first one is ' D '.
(All the angles inside a triangle have to add up to exactly 180 degrees.)
The answer to the second one is ' C ' .
(If two sides are equal, then the sides opposite them are also equal.)